Numerical studies on the effects of the channel-inlet-pressure difference in the pressure-retarded osmosis (PRO) power system - Hong, S.S.; Ryoo, W.; Chun, M.-S.; Chung, G.Y. (Korean Institute of Chemical Engineers, 2014)
In the spiral wound module of the pressure-retarded osmosis (PRO) system for the salinity gradient power generation, effects of the inlet pressure differences between feed-channel and draw-channel were studied. Fluxes of water and solute through membrane and power were estimated. The water flux through membrane decreased along the x-direction and increased along the y-direction with the increase of inlet pressure differences between two channels. On the other hand, the solute flux through membrane showed the opposite trend. The concentration of flow in the feed-channel increased a lot along the y-direction and that in the draw-channel decreased along the x-direction. In our system, for the inlet pressure differences of 1∼11 atm, the flow rate in the feed-channel decreased about 8∼13% and that in the drawchannel increased by the same amount. The power density increased and then decreased with the increasing inlet pressure difference.